Concealed Intradural Disc Herniation: A Case Report - Hammad, Ahmed; Geiger, Florian; Redder, Andreas; Oberbeck, Kai; Ardeshiri, Ardavan; Wirries, Andre (Archives of Clinical and Medical Case Reports, 2020)
Introduction: We present a case of a concealed intradural lumbar disc herniation following a previous discectomy with adhesions of the ventral dura to the posterior longitudinal ligament. Case Presentation: A 40-year-old Asian male with a lumbar discectomy 2 years ago presented to our emergency department with over the last few days rapidly progressing neurological symptoms of the lower limbs. The patient was admitted and MRI was performed on an emergency basis. Due to severe pain, and as a result the patient inability to lie down to complete the MRI examination, the MRI scan was incomplete. However, it showed an occupying mass at the level L4/5 with suspected recurrent disc herniation. Intraoperative only a small herniation was found. A new MRI, performed shortly after the 1st surgery, revealed an intradural herniation that could be addressed by microscopic durotomy and sequestrectomy. Because of persisting weakness and pain a new MRI scan was done and revealed a recurrent intradural hernia proximal to the durotomy. Revision surgery was indicated and performed successfully. The 6 months follow-up MRI scan revealed no signs of recurrence. The clinical examination, 6 months postoperatively, showed almost complete remission of the preoperative weakness and pain with restoration of the walking ability. Discussion: Most literature addressing the pathophysiology of intradural lumbar disc herniation are cadaveric studies. Currently only few case reports or series discuss this pathology. Different theories including ‘mechanical compression’ and ‘adhesions’ theories have been discussed. A solid proof couldn’t be provided. Our patient had a previous discectomy at the same segment two years ago. The MRI scans could clearly show scar tissue on this level with a direct connection of the lumbar disc to the intradural compartment. We believe that e